Crack cocaine users views regarding treatment with contingency management in Brazil - André Q. C. Miguel; Clarice S. Madruga; Viviane Simões; Rodolfo Yamauchi; Claudio J. da Silva; Renata R. Abdalla; Michael McDonell; Sterling McPherson; John M. Roll; Jair J. Mari; Ronaldo R. Laranjeira (BMC, 2018)
Abstract Background Contingency management (CM) has recently shown efficacy in promoting abstinence and retention in treatment among crack cocaine users in Brazil. However, partially because of unawareness and resistance among health care providers, CM has not been widely employed. The objective of this study was to conduct a secondary analysis in order to evaluate how CM participants perceive their treatment experience. Methods Twenty-seven crack cocaine users, previously assigned to 12 weeks of CM treatment, were assessed with a structured questionnaire designed to assess their personal opinion of, difficulty in understanding, and acceptance of the CM intervention, as well as their opinion regarding its impact on their treatment responses. Results Descriptive analyses showed that 92.6% of the participants found it very easy to understand the CM protocol. All participants reported liking their CM experience quite a bit. For the perceived effects of CM on their treatment response, 81.5% of the participants stated that CM helped them considerably, the mean score for the impact of CM on treatment response (out of a maximum of 10) being 9 (SD = 1.5). When asked if they believed CM could help other people with crack cocaine dependence, 92.6% of the participants stated that CM could help such people a lot and 7.4% stated that it could help them a little. Conclusions From the perspective of the patients, CM was easily assimilated, easily accepted, and had a direct positive effect on treatment response. These findings provide additional support for the incorporation of CM into substance abuse treatment services in Brazil.